2008
DOI: 10.1007/s11738-008-0251-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses to drought stress in mulberry (Morus alba L.): evaluation of proline, glycine betaine and abscisic acid accumulation in five cultivars

Abstract: Five popularly grown mulberry cultivars (K-2, MR-2, TR-10, BC2-59 and S-13) were subjected to drought stress by withholding irrigation, to obtain leaf water potentials (W w ) ranging from -0.75, -1.50 and -2.25 MPa. Accumulation of proline, glycine betaine and abscisic acid (ABA) were quantified in control and water stressed mulberry leaves. The activities of enzymes involved in proline accumulation including glutamate dehydrogenase (EC1.4.1.2-4), pyrroline-5-carboxylate synthetase (EC 1.2.1.41), pyrroline-5-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…P5CS and PDH activity was not affected by drought stress and PBZ treatment. Chaitanya et al (2009) reported that PDH and P5CS activity increased in the mulberry under drought stress which was followed by increase in proline accumulation. On the contrary, in this study no correlation was observed between enzyme activity and proline accumulation.…”
Section: Discussionmentioning
confidence: 98%
“…P5CS and PDH activity was not affected by drought stress and PBZ treatment. Chaitanya et al (2009) reported that PDH and P5CS activity increased in the mulberry under drought stress which was followed by increase in proline accumulation. On the contrary, in this study no correlation was observed between enzyme activity and proline accumulation.…”
Section: Discussionmentioning
confidence: 98%
“…The activities of antioxidant enzymes under water stress vary among plant species or cultivars (Chaitanya et al 2009). The sensitivity of the enzymatic response depends on intrinsic genetic traits in plants.…”
Section: Antioxidation Enzymesmentioning
confidence: 99%
“…Proline accumulation in stress conditions was not only dependent on the type of stressor but also the plant species. In addition, the ornithine-δ-aminotransferase (δ-OAT), glutamate dehydrogenase (GDH), and proline-5-carboxylase reductase (P5CR) in the proline biosynthesis pathway in drought-stressed mulberry (Chaitanya et al, 2009) and Sesuvium portulacastrum (Slama et al, 2006) have been investigated. In this study, REL in oil palm seedlings was increased under PEG-and mannitol-induced osmotic stress, as was proline accumulation.…”
Section: Growth Performancementioning
confidence: 99%